Stimulus-response coupling in sponge cell aggregation: Evidence for calcium as an intracellular messenger - Dunham, Philip (1983)
Aggregation of dissociated sponge cells has been proposed as a model for cell-cell recognition mediated by a specific proteoglycan aggregation factor (Microciona aggregation factor). To test whether sponge cells undergo stimulus-response coupling in which intracellular Ca is a messenger, aggregation of mechanically dissociated cells was studied. Changes in light transmission through cell suspensions paralleled aggregation as judged by microscopy. In the presence, but not absence, of Ca (>5 mM) partially purified Microciona aggregation factor aggregated both living and glutaraldehyde-fixed cells. Evidence for a messenger role of Ca was the following: (i) Addition of Ca to Ca-depleted cells induced aggregation that varied with [Ca]. (ii) Addition of Ca ionophores (A23187 and ionomycin) caused aggregation that varied with [Ca] and far exceeded that provoked by Ca alone. Glutaraldehyde-fixed cells did not respond to ionophores with or without Ca. (iii) Calcium antagonists inhibited aggregation. These included inhibitors of the Ca-calmodulin complex (N-(6-aminohexyl)-5-chloro-1-naphthalenesulfonamide hydrochloride and 1-[bis(p-chlorophenyl)methyl]-3-[2,4-dichloro-β-(2,4-dichlorobenzyloxyl)phenylethyl]imidazolinium chloride), Ca channel blockers (La, Co, Cd, and verapamil), and three nonsteroidal anti-inflammatory agents (indomethacin, ibuprofen, and piroxicam). Results indicated not only that early events of sponge aggregation can be quantified by continuous recording but that aggregation is not simply due to passive agglutination of inert cells by an extracellular proteoglycan. Rather, sponge cells recognize surface ligands to which they respond by Ca-dependent stimulus-response coupling.